2022
DOI: 10.3390/ph15040443
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterisation of Bacteriophage Selective for Key Acinetobacter baumannii Capsule Chemotypes

Abstract: Nineteen bacteriophages against five main capsular types of multidrug-resistant Acinetobacter baumannii were isolated from tertiary care hospital sewage. Eight representative phages from each capsular type were characterized and tested for their biological properties. The biological features revealed that phages T1245, T444, and T515 had a large burst size of more than 420 pfu/mL, together with a short latent period lasting less than 6 min, and were readily adsorbed to a bacterial host within 10 min. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Capsules can mask receptors present on the cell surface, and thus act as barriers to phage infection 1 , 2 , 78 . They can also be necessary for phage infection, especially in nearly ubiquitously capsulated species like Serratia 79 , Acinetobacter 21 or Klebsiella 24 . The host range of capsule-targeting phages is generally restricted to one or a few serotypes 17 , 24 because they rely on the tail spike proteins harbouring depolymerase enzymes 19 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Capsules can mask receptors present on the cell surface, and thus act as barriers to phage infection 1 , 2 , 78 . They can also be necessary for phage infection, especially in nearly ubiquitously capsulated species like Serratia 79 , Acinetobacter 21 or Klebsiella 24 . The host range of capsule-targeting phages is generally restricted to one or a few serotypes 17 , 24 because they rely on the tail spike proteins harbouring depolymerase enzymes 19 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Capsules can mask receptors present on the cell surface, and thus act as barriers to phage infection [85][86][87]. They can also be necessary for phage infection, especially in nearly ubiquitously capsulated species like Serratia [88], Acinetobacter [89] or Klebsiella [24]. The host range of capsule targeting phages is generally restricted to one or a few serotypes [24,90], because they rely on the tail spike proteins harbouring depolymerase enzymes [91,92] that act as specific receptor-binding proteins tunnelling through capsules [93].…”
Section: Discussionmentioning
confidence: 99%
“…In many cases phages are blocked by the obstacle caused by the capsule and cannot reach their cell receptor [2,16]. Yet, some phages have evolved mechanisms to bypass the capsule barrier, such as encoding hydrolases called depolymerases which digest the capsule [17][18][19][20][21][22]. Such phages can recognize and attach to capsules of the serotype for which they encode a depolymerase.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…There was no phage activity at extreme conditions of temperature (<21°C and >45°C) and pH (<6 and >8). Studies have reported that viability at pH<4 and >9 and temperatures < 15°C is one of the most common limiting factors for phage activity 20,21 . Phages are generally more temperature and pH-resistant compared to their host bacteria 22 .…”
Section: Fig 3: Effect Of Different Temperatures On the Stability And...mentioning
confidence: 99%